Higher Training Frequency Is Important for Gaining Muscular Strength Under Volume-Matched Training - Ochi, Eisuke; Maruo, Masataka; Tsuchiya, Yosuke; Ishii, Naokata; Miura, Koji; Sasaki, Kazushige (Frontiers in Physiology, 2018)
Background: This study investigated the effect of volume-matched strength training programs with different frequency and subsequent detraining on muscle size and strength. Methods: During a training period of 11 weeks, untrained subjects (age: 22.3 ± 0.9 years, height: 173.1 ± 4.8 cm and body mass: 66.8 ± 8.4 kg) performed knee-extension exercise at 67% of their estimated one-repetition maximum either one session per week (T1 group: 6 sets of 12 repetitions per session; n = 10) or three sessions per week (T3 group: 2 sets of 12 repetitions per session; n = 10). Rating of perceived exertion (RPE) and muscle stiffness were measured as an index of muscle fatigue and muscle damage. The magnitude of muscle hypertrophy was assessed with thigh circumference and the quadriceps muscle thickness. The changes in muscle strength were measured with isometric maximum voluntary contraction torque (MVC). Results: During the training period, RPE was significantly higher in the T1 than in the T3 (p < 0.001). After 11 weeks of training, both groups exhibited significant improvements in thigh circumference, muscle thickness, and MVC compared with baseline values. However, there was a significant group difference in MVC at week 11 (T1: 43.5 ± 15.5%, T3: 65.2 ± 23.2%, p < 0.05). After 6 weeks of detraining, both groups showed the significant decreases in thigh circumference and muscle thickness from those at the end of training period, while no significant effect of detraining was observed in MVC. Conclusions: These results suggest that three training sessions per week with 2 sets is recommended for untrained subjects to improve muscle strength while minimizing fatigue compared to one session per week with 6 sets.